Apuntes sobre el poeta Richard Rognet - Bergasa, Grégoire (Anales de Filología Francesa, 2009)
In these few pages, we have tempted to build up a poetic itinerary which enables the reader to discover one of the great voices belonging to French contemporary poetry. After presenting his life briefly, we have followed the traces of the words used in Rognet’s poetry. Hidden under the immutability of his words rises up the poetic strength of his writing, energizing the primitive semantics of the words in order to combine man’s daily life, his present as well as his universal and even divine nature. The poet reveals all the voices which are deeply hidden in his heart, thus bringing to light a new meaning “balancing on the lightning”as he himself writes. Thus, his words become a stage on which man’s inner nature and the world are on display. This stage direction gives birth to the one whose name is Lord of the words. The latter is to be found throughout his text in which various voices mix together, including his own voice in the process of construction, the voices of his ancestors and the voices of his readers building up an actantial model in which the missing “deus ex maquina”soon appears when the emotion, the pathos becomes unbearable, when escaping through the gardens, the balconies, the stairs and the windows becomes vain. Indeed, the poetic voice itself turns into a prison, expressing itself through the brevity and the freedom of the verses, leaving a feeling of void and silence. Thus, the poetic body is being built in order to catch what is escaping from the human body of the poet. In the dead of this silence lies the magical place of childhood, a place one is tempted to imprison but witch can keep its secret. In his struggle to reach the depths of childhood, the words of the poet become metaphysical and a god, often ignored, appears as an ultimate answer which gives rise to a landscape marked by the memory, the dream and the eternity, finally fading away and giving way to an ever victorious silence and to the reader…